Mixed Speech Styles in Two Single-Gendered Occupational Groups: Identities in Interaction - Pinkevičienė, Dalia (Taikomoji kalbotyra, 2022)
This paper qualitatively examines mixed speech styles within the context of two single-gendered white-collar Lithuania-based workplaces situated in Vilnius: an IT company and a company producing cosmetics (COSM). In Lithuanian contexts, mixed speech styles could be broadly defined as a flow of speech consisting of linguistic resources from languages other than Lithuanian (mainly English and Russian) incorporated into otherwise Lithuanian talk. The paper focuses on situated usage of mixed speech styles employed in talk at work. It aims to see how the linguistic enactment of mixed speech styles varies according to the working team and how such variation may influence the construction of participants’ complex identities. The research is based on naturally occurring recorded speech, and the method applied could be determined as ethnographically informed Interactional Sociolinguistics. The analysis shows that the two single-gendered communities of practice examined do not draw on the same non-native linguistic resources and that such dissimilar speaker choices and identity work can be predetermined by an intricate interplay of social and situational factors.
Keywords: mixed speech; workplace discourse; identity construction; communities of practice